MODEL OF TECHNOLOGY VALUATION SYSTEM OF PATENT-ORIENTED PROCESS (CASE STUDY ON COMPOSITION OF CAJUPUT CANDY AS THROAT RELIEF) - Budi Dharmawan, Sukardi, Krisnani Setyowati (Department of Agroindustrial Technology, Bogor Agricultural University, 2010)
ABSTRACT Determining value and predicting price of a technology is difficult to be done in the process of commercialization because invention’s character in the form of technology could not be measured quantitatively (intangible). This character complicates process valuation of technology. Based on that, technology valuation system was expected to be able to assist inventor and intellectual property rights center in assessing and predicting the price of new technology. The objectives of this research were (1) to value composition of cajuput candy as throat relief as new technology that is potential to be commercialized; and (2) to give license price prediction for composition of cajuput candy as a throat relief product. Inventor and investor have different perception in assessing new technology. This perception identified its variables and attributes. Rank of technological valuation variables was carried out with Ordered Weighted Averaging-Operator method. Commercialization risk judgement was done with Expert Panel method. Technological license price prediction was done with Discounted Cash Flow method. Assessment and prediction of technological license price was done with system approach in decision making with program package called V-Tech v1.2. Based on the analysis result the composition of cajuput candy as throat relief had risk factor of 0.4947 with technology class in moderate risk, stayed at growth step in technological life cycle and stayed at diffusion step in product life cycle. License profit was equal to Rp 111,701,422.00 and stayed at growth step in innovation diffusion to new consumer. Keywords: valuation system, cajuput candy, license profit, risk factor, technology life cycle, product life cycle